Internet of Things (IoT) Embedded Future Supply Chains for Industry 4.0: An Assessment from an ERP-based Fashion Apparel and Footwear Industry - Aabid Abdul Majeed; Thashika D Rupasinghe (International Journal of Supply Chain Management, 2017)
In this competitive business world most of the supply chains are struggling to sustain competitively in the global supply chain due to its increasing complexity in each phase of the supply chain operations. Many companies are facing financial difficulties and some have shut down due to poor supply chain management practices. Companies have to be smarter by incorporating the necessary technologies to be more competitive and sustain in the global supply chain, that processes can be better managed and automated where necessary. Most companies fail due to poor integrations of technology in their supply chain. It is important that companies be smarter in order to strive hard to reduce cost, improve customer services and to increase return of investments throughout the supply chain. While a few industries are taking a major leap; it is vital for other companies to adopt to the changing nature of the digital supply chains and embrace industry 4.0, leveraging Internet of Things (IoT). The primary goal of this study is to improve inbound and outbound operations to better manage and optimize and automate operations in an ERP system through the use of RFID technology and Business Application Programming Interface (BAPI) technology in SAP. The existing ERP system was thoroughly analyzed using mixed method approach and was followed-up in assessing how transactions can be better executed in the system. The study derives a conceptual framework to enhance inbound and outbound operations in ERP for Fashion Apparel and Footwear Industry.